2021
DOI: 10.1136/neurintsurg-2021-017806
|View full text |Cite
|
Sign up to set email alerts
|

The ARTISSE intrasaccular device for intracranial aneurysm treatment: short-term, mid-term and long-term clinical and angiographic results

Abstract: BackgroundThe concept of intra-aneurysmal flow disruption has emerged as a new paradigm for the treatment of primarily bifurcation aneurysms. The purpose of this study was to determine the clinical and angiographic outcomes of patients treated with the new ARTISSE intrasaccular device (ISD).MethodsSelected patients with bifurcation aneurysms that matched the indications of the ARTISSE ISD defined by the manufacturer were treated in a single center. Clinical and angiographic follow-up was conducted at 6 and 36 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The WEB clinical assessment of intrasaccular aneurysm therapy (WEBCAST), the French Observatory, WEBCAST 2, WEB-IT, ARTISSE ISD and the contour neurovascular system european pre-market unruptured aneurysm study. [35][36][37][38] Preliminary results demonstrated a high level of procedural safety and technical success.…”
Section: Discussionmentioning
confidence: 96%
“…The WEB clinical assessment of intrasaccular aneurysm therapy (WEBCAST), the French Observatory, WEBCAST 2, WEB-IT, ARTISSE ISD and the contour neurovascular system european pre-market unruptured aneurysm study. [35][36][37][38] Preliminary results demonstrated a high level of procedural safety and technical success.…”
Section: Discussionmentioning
confidence: 96%
“…The Nautilus Intrasaccular System (EndoStream Medical, Or Akiva, Israel) is a novel intrasaccular device unavailable in the USA that has demonstrated low complication rates without the need for antiplatelet therapy in ruptured aneurysms [ 76 ]. The novel ARTISSE (Medtronic, Irvine, CA, USA) intrasaccular device, which is also not available in the USA, demonstrated thromboembolic complications in two out of the nine unruptured cases performed [ 77 ]. These patients were placed on antiplatelet therapy to prevent further strokes.…”
Section: Discussionmentioning
confidence: 99%
“…Luna named Artisse in the newest version (5,62). Previous studies showed that the Luna/Artisse embolization system was safe and effective (86,87). However, further study with a large sample is needed.…”
Section: Luna/artisse Embolization Systemmentioning
confidence: 99%